2007
DOI: 10.1038/sj.leu.2404820
|View full text |Cite
|
Sign up to set email alerts
|

Circulating angiopoietin-2 is a strong prognostic factor in acute myeloid leukemia

Abstract: Angiogenesis plays an important role in solid tumors and hematologic malignancies. The angiopoietins act as essential regulators in this process. We investigated the impact of circulating angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2) and soluble Tie2 (sTie2) on overall survival in patients with acute myeloid leukemia (AML). Ang-1, Ang-2 and sTie2 were measured in plasma samples from 68 AML patients and 11 controls using enzyme-linked immunosorbent assay. Circulating levels of Ang-2 and sTie2 (median (range): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 38 publications
8
46
2
Order By: Relevance
“…Our findings are in line with a recent observation of elevated Ang-2 and Tie-2 levels in patients with chronic myeloid leukemia (CML) and multiple myeloma [14]. It was found that blood levels of sAng-2 and sTie-2 were strongly associated with the extent of BM infiltration, TLC and LDH, providing indirect evidence that the leukemic blasts themselves at least significantly contributed to the plasma levels of the tested angiogenic factors [19]. Furthermore, a strong correlation could be demonstrated between plasma levels of Ang-2 and Tie-2 and the overall survival in AML patients after chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are in line with a recent observation of elevated Ang-2 and Tie-2 levels in patients with chronic myeloid leukemia (CML) and multiple myeloma [14]. It was found that blood levels of sAng-2 and sTie-2 were strongly associated with the extent of BM infiltration, TLC and LDH, providing indirect evidence that the leukemic blasts themselves at least significantly contributed to the plasma levels of the tested angiogenic factors [19]. Furthermore, a strong correlation could be demonstrated between plasma levels of Ang-2 and Tie-2 and the overall survival in AML patients after chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, it is entirely possible that a predominant proportion of circulating Ang-2 could be secreted by activated BM endothelial cells, given the increased angiogenic activity in the leukemic BM. Furthermore, it is conceivable that Ang-2 could also be released by the endothelium of the normal vasculature upon dysregulated stimulation by leukemic blasts [19]. Our findings are in line with a recent observation of elevated Ang-2 and Tie-2 levels in patients with chronic myeloid leukemia (CML) and multiple myeloma [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are a few studies on serum Ang-1 levels, and these have reported conflicting results. Compared with the level in controls, the serum Ang-1 level was elevated in breast cancer [25] but lower in thyroid cancer [26]; the level was similar to the control level in prostate cancer [25] and acute myeloid leukemia [27].…”
Section: Introductionmentioning
confidence: 54%
“…The tissue expression level of Ang-2 is related to the stage progression and overall survival [23,24]. Serum Ang-2 has also been reported to be increased in breast cancer [25], prostate cancer [25], thyroid cancer [26], acute myeloid leukemia [27], and lung cancer [28], with prognostic implications in the latter two cancers.…”
Section: Introductionmentioning
confidence: 99%